Investigation of pressure variation of airflow over riblets - Tan, Keith Jie Wei (2019)
In the globalising world with growing demand of cheaper and more efficient mode of travelling. A commonly discussed solution is reducing the fluid drag experienced by everyday objects. Many studies have turned to observing the nature for inspiration and riblets surfaces inspired by the sharks’ skin is one of the most studied and experimented. As riblets can have very different geometries, despite numerous studies on riblets, some geometries are lacking in experimental data and requires further verification regarding its effectiveness. In this report, the fabrication process of the Thin Blade surfaces on Aluminum test plates through wire cutting electro-discharge machining technology are documented. The dimensions of the riblets followed closely to the optimum thickness-to-spacing and height-to-spacing ratio found in previous researches in water and oil channels but with different spacings for the test pieces. The riblets will be tested in a closed loop wind tunnel to observe for the variation in pressure drop across the surface to determine whether drag reduction is achieved. The results are conclusive that the t/s and h/s ratio found in oil and water channels are applicable to reduce pressure drop in airflow as well. It is observed that more pressure drop reduction are achieved with lesser spacings and reduction can be negligible with large spacings despite having riblets surfaces. The trend also suggested that in the Laminar flow, riblets have minimal effects on the pressure drop and pressure drop can only be detected in the Turbulent region.